The Effectiveness of Blended Learning on Practical Application Types in Natural Sciences in SMP Muhammadiyah 4 Gempol - Avivatul Abidah; Ria Wulandari (Proceedings of The ICECRS, 2020)
This research aims to know the effectiveness of Blended Learning type practical application in Natural Science Education subjects in SMP Muhammadiyah 4 Gempol. Research is a descriptive quantitative study with the research design of one-group-pre test-post test. The research sample amounted to 19 students from class VIII B. The instruments used in this study are study-management sheets, student activity sheets, student response sheets and student learning outcomes. The data analysis technique of learning implementation using the formula of Percentage of agreement, student activity using activity calculation techniques, student response using the technique of response analysis and learning results using N-Gain. The results of the study gained from the implementation of learning by 95% in good category, student activity of active value and positive response is superior, and test of learning results successfully increased with a percentage of compensation ≥ 85%. Thereby learning Blended Learning by using Moodle learning apps is said to be effective.